Faktor – Faktor Yang Berhubungan Dengan Keikutsertaan Ibu Dalam Imunisasi MR (Meales Rubella) Pada Anak Usia 9 Bulan – 15 Tahun Di Desa Muara Musu Wilayah Kerja Puskesmas Rambah Hilir 1 - Junita, Elfira (Jurnal Martenity and Neonatal, 2019)
Immunization is one way to increase a persons imunity to an antigen so that if it is later exposed to antigens that may not accur the disease. MR immunization is a way to prevent meales rubella. The purpose of this study is to knowing Factors related to the participation of the mothers in MR (Meales Rubella) immunization in children aged 9 months to 15 years in the village of muara musu the working area 0f the health center rambah downstream 1. The method used is a quantitative analytic approach cross sectional. The population in this study amounted to 120 with a total sampel of 50 peopl. The sample technique used is simple random sampling. The analysis used in this study is univariate and bivariate analysis using the chi square test.